West Nile virus activity in United States blood donors and optimizing detection strategies: 2014‐2018. Issue 1 (12th December 2019) - Groves, Jamel A.; Foster, Gregory A.; Dodd, Roger Y.; Stramer, Susan L.
Abstract : BACKGROUND: Rare transfusion‐transmitted West Nile virus (WNV) cases usually occur due to gaps in testing involving converting to more sensitive nucleic acid testing (NAT) formats (referred to as triggering). Using data from 2014 to 2018, we investigated a strategy used to increase detection early in the triggering period and reviewed its yield as the individual donation (ID)‐NAT geographic area was decreased. METHODS: Mini‐pool–NAT transitioned to ID‐NAT following triggering based on one WNV NAT–reactive donation (having an elevated signal, repeat reactive, or in an area with WNV ongoing activity). ID‐NAT–triggered geographic areas included an entire state (2014‐2017) or collections within a 50‐mile radius of the triggering donor's residential zip code (2018). During the MP‐ to ID‐NAT transition, donation samples were retrieved and tested by ID‐NAT for those with results not yet released (referred to as in‐process testing). Reactive sample confirmation was performed by repeat NAT of an independent sample or antibody testing. RESULTS: ID‐NAT included 3.2 million donations of more than 25 million tested year‐round, resulting in 684 confirmed positives; all confirmed‐positive donations occurred from June to December (0.64/10, 000). Overall, 52% (358/684) required ID‐NAT for detection, including 68 (19%) antibody negatives. Ten of 19 (53%) identified in‐process were ID‐NAT–only detectable, including four antibody negatives, or approximately 1 per year (2.8% of ID‐NAT–only detectable). With reduced triggering geography, 12 of 19 (63%) were not identified (including 6/10 ID‐NAT–only detectable, and 2/4 ID‐NAT–only detectable/antibody negative). CONCLUSION: WNV NAT's utility is between June–December; however, abandoning testing outside of this time may increase risk. While in‐process testing identified approximately one ID‐NAT–only detectable (antibody‐negative) donation per year, reducing the geographic triggered area decreased its effectiveness.